Design and synthesis of threading intercalators to target DNA - Howell, Lesley A.; Gulam, Rosul; Mueller, Anja; O’Connell, Maria A.; Searcey, Mark (Bioorganic & medicinal chemistry letters, 2010)
Threading intercalators are high affinity DNA binding agents that bind by inserting a chromophore into the duplex and locating one group in each groove. The first threading intercalators that can be conjugated to acids, sulfonic acids and peptides to target them to duplex DNA are described, based upon the well studied acridine-3- or 4-carboxamides. Cellular uptake of the parent acridine is rapid and it can be visualized in the nucleus of cells. Both the parent compounds and their conjugates maintain antitumor activity.